2012
DOI: 10.1111/j.1476-5381.2012.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport and pharmacodynamics of albitiazolium, an antimalarial drug candidate

Abstract: BACKGROUND AND PURPOSE Choline analogues, a new type of antimalarials, exert potent in vitro and in vivo antimalarial activity. This has given rise to albitiazolium, which is currently in phase II clinical trials to cure severe malaria. Here we dissected its mechanism of action step by step from choline entry into the infected erythrocyte to its effect on phosphatidylcholine (PC) biosynthesis. EXPERIMENTAL APPROACH We biochemically unravelled the transport and enzymatic steps that mediate de novo synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…At physiological pH, most of the ammonium is in the NH 4 ϩ form and thus requires transport proteins for membrane passage. As for other inorganic or organic cations (choline, tetramethylammonium, or tetrapropylammonium) (18,36,37) and for albitiazolium, (18), NH 4 ϩ ion transport should be mediated by the new permeability pathways (NPP) and thus at least partly inhibits albitiazolium entry. Alternatively, presence of NH 4 ϩ ions in the host cytosol could change pump activities and thus ionic gradients, altering the transports dependent on these gradients and leading to inhibition of albitiazolium entry into IRBC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At physiological pH, most of the ammonium is in the NH 4 ϩ form and thus requires transport proteins for membrane passage. As for other inorganic or organic cations (choline, tetramethylammonium, or tetrapropylammonium) (18,36,37) and for albitiazolium, (18), NH 4 ϩ ion transport should be mediated by the new permeability pathways (NPP) and thus at least partly inhibits albitiazolium entry. Alternatively, presence of NH 4 ϩ ions in the host cytosol could change pump activities and thus ionic gradients, altering the transports dependent on these gradients and leading to inhibition of albitiazolium entry into IRBC.…”
Section: Resultsmentioning
confidence: 99%
“…2C) within the first 15 min of incubation in drug-free medium likely corresponded to the release of the minor portion of drug contained in the erythrocyte cytosol of IRBC, which might have been released or reexported into the external medium via parasite-induced NPP in the erythrocyte membrane (37). We recently showed that albitiazolium enters IRBC mainly through these NPP (18), which can transport molecules bidirectionally (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bisthiazolium salts exert their antimalarial activity through inhibition of de novo PC biosynthesis by blocking the parasite choline carrier (10)(11)(12)). An additional interaction with heme inside the food vacuole contributes to the antimalarial activity (13).…”
mentioning
confidence: 99%